Contribuição aos estudos da influência da nanossílica nas propriedades mecânicas e na trabalhabilidade de concretos para produção em centrais e para fabricação de pré-moldados - Moraes, Mayara Queiroz (2012)
Unlike the silica fume, whose benefits on the properties of the concretes are already widely known, little is known regarding nanosilica. This research offers an analysis of the contribution of different types of nanosilica in mechanical characteristics and workability maintenance of concretes, as well as an evaluation of the behavior of these additions when subjected to steam curing. For this, there were compared among themselves laboratory test results in concretes with different characteristics and different purposes (one of them suitable for production at batching plants and the other for metering precast elements). The results confirmed advantages for the simple addition of nanossílica at mechanical properties of concretes for batching plants with strengths above 40 MPa (a/c<0.52), but showed that the most advantageous situation consists in adding it together with sílica fume, since the concrete with both additions exceeded the reference concrete above 36 MPa (a/c<0.615), which highlights the importance of combining pozzolanic effect of silica fume, the creation of nucleation sites caused by nanossílica and better packaging mix, size distribution generated by the two additions give the folder.Regarding the maintenance of workability, the nanosilica dispersed in superplasticizer demonstrated satisfactory performance. In the analysis of concretes for precast elements, the addition of nanosilica dispersed superplasticizer and silica fume together was also the one which showed the best results in terms of resistance in 28 days of conventional curing. However, with steam curing, a great improvement was noted in the behavior of nanosilica dispersed in water, which had not achieved good results with the conventional cure, while nanosilica dispersed in superplasticizer did not respond well to the process, possibly due to the shape of the polycarboxylate used in the dispersion of the particles. Probably, the nanosilica dispersed in water showed no significant pozzolanic activity levels, but with the rise of temperature and the agitation of the particles, the formation of nucleation sites was intensified. As the development of resistance in early ages, all additions had positive effects, but the best performance was observed on the concrete with the simple addition of nanosilica dispersed in superplasticizer. With this addition, the concrete has reached 40 MPa after only 12 hours of steam curing, within about four times lower than the reference concrete (44 hours), which suggests that its addition to the concrete could result in na almost four times greater productivity of a precast elements factory.